(untitled) (Informatica, 2021)
Maritime shipping is a complex process because it requires a continuous analysis of huge amounts of information. Much of this information has variable spatial and temporal properties. In addition, the analysis must be effective to help in making decisions in a timely manner. Generally the analysis is applied with Spatial On-Line Analytical Processing (SOLAP) basing on spatial data warehouses SDW. Data warehousing by current technologies with relational database management systems (RDBMS) cannot be applied effectively to manage the increasing complexity and volume of geo-referenced data. In order to increase the performance and availability of services, NoSQL databases technologies have appeared. This paper presents the modeling and the realization of a spatial decision support system (SDSS) for maritime navigation namely “Maritima”, basing on the integration of the ECDIS and OLAP systems. In fact, the spatio-multidimensional analysis of the stored data can benefit from the expressive power of the electronic navigation chart offered by the ECDIS system. In order to benefit from the NoSQL model advantages, we try to apply transformations for the conceptual model to create document NoSQL DW for maritime data. In addition to that, the multidimensional analysis at different dimensions and aggregation levels can generate beneficial indicators for the decision-aid and can be very useful in addition of other steering systems for secure maritime navigation. Finally, “Maritima” is tested with a set of spatial data related to two different harbors “Arzew” and “Oran” in western of Algeria.